A step towards green concrete: Effect of waste silica powder usage under HCl attack. (1st July 2018) - Hendi, Ali; Behravan, Amir; Mostofinejad, Davood; Sedaghatdoost, Arash; Amini, Morteza
Abstract: The durability of environment-friendly concrete containing two types of waste material is investigated. Glass powder and microsilica with high silica content were selected to compare their effects on the durability of self-consolidating concrete (SCC) and ordinary concrete with the same packing density in the acidic medium. Experimental results show that microsilica and glass powder do not contribute to concrete corrosion reduction and the most important variable would be superplasticizer content. According to this result, ordinary concretes with lower superplasticizer content show better performance in HCl medium than SCCs. For a quantitative analysis and even to elicit the optimum values for minimum corrosion from the experimental results, an artificial neural network (ANN) and particle swarm optimization (PSO) were used. The minimum mass-loss was related to 15.68% for the volume of permeable pores and the optimum value for compressive strength would be in the range of 32–34 MPa. Graphical abstract: Highlights: SCC samples with denser structure are more vulnerable than OC ones. There is an optimum amount of C-S-H to resist HCl attack. Microsilica, glass powder and superplasticizer make concrete more susceptible to HCl medium. The optimum value of volume of permeable pores derived to be about 15 percent.